Study on Marketing Efficiency of Rapeseed and Mustard crop in Jaipur district of Rajasthan, India - Yadav, Mukesh Kumar; Sharma, Amod; Kumar, Ajay; Nakhro, Rokoneituo (International Journal of Economic Plants, 2018)
Rajasthan, one of the major rapeseed and mustard producing states in India, predominantly cultivate Indian mustard (Brassica juncea L.). The present study conducted in Jaipur district of Rajasthan reveals that per hectare marketed surplus was found out to be highest (2212.50 q) on medium farms, followed by 1142.80 q and 145.50 q on small and marginal farm, as the marketed surplus was higher than marketable surplus for all size group of farmers. Two marketing channels were identified viz., channel I: Producer-Consumer and channel II: Producer-Retailer-Consumer. Pattern of disposal showed that channel II was the most effective for marginal, small and medium groups viz., they transacted 80.34, 71.50 and 77.25 % of their marketed surplus through this channel. The cost incurred by intermediaries was 27.29 % of the total marketing cost in channel II. Producer share in consumer rupees’ was found higher on channel I (94.33 %) due to the absence of intermediaries as compared to channel II (91.73 %).